How Entrepreneurs Use Symbolic Management to Acquire Resources - Zott, Christoph; Huy, Quy Nguyen (Administrative Science Quarterly, 2007)
Results of a two-year inductive field study of British ventures show that entrepreneurs are more likely to acquire resources for new ventures if they perform symbolic actions—actions in which the actor displays or tries to draw other people's attention to the meaning of an object or action that goes beyond the object's or action's intrinsic content or functional use. We identify four symbolic action categories that facilitate resource acquisition: conveying the entrepreneur's personal credibility, professional organizing, organizational achievement, and the quality of stakeholder relationships. Our data show that entrepreneurs who perform a variety of symbolic actions from these categories skillfully and frequently obtain more resources than those who do not. Our data also suggest three factors—structural similarity, intrinsic quality, and uncertainty—that moderate the relationship between symbolic management and resource acquisition. We theorize how the various symbolic action categories shape different forms of legitimacy that help entrepreneurs acquire resources.